2021
DOI: 10.1016/j.jtemb.2020.126656
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke is a likely source of lead and cadmium in settled house dust

Abstract: Introduction: Environmental exposure to lead (Pb) and cadmium (Cd) are risk factors for adverse health outcomes in children and adults. This study examined whether thirdhand smoke residue contributes to Pb and Cd in settled house dust. Methods: Participants were 60 multiunit housing residents in San Diego, California. All had indoor smoking bans during the study period, and 55 were nonsmokers. Wipe samples from different surfaces and vacuum floor dust samples were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Higher lead levels among the participants who had passed away could be due to the higher proportion of smokers in the group. Cigarette/tobacco smoke has been demonstrated as one of the routes of environmental exposure to heavy metals, including lead since the heavy metals from the soil are usually absorbed and accumulated in the plant tissues of tobacco [ 38 ]. Indeed, we found that the lead levels in smokers’ hair samples were significantly higher than in non-smokers (4.94 vs. 4.23 μg/g; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Higher lead levels among the participants who had passed away could be due to the higher proportion of smokers in the group. Cigarette/tobacco smoke has been demonstrated as one of the routes of environmental exposure to heavy metals, including lead since the heavy metals from the soil are usually absorbed and accumulated in the plant tissues of tobacco [ 38 ]. Indeed, we found that the lead levels in smokers’ hair samples were significantly higher than in non-smokers (4.94 vs. 4.23 μg/g; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…These types of misclassifications could serve to reduce the apparent difference in Cd between groups exposed to less smoke and the current smoking group. We do not account for other potential Cd exposures sources, such as house dust [ 41 ], occupation, or diet; however, we know that dietary contribution to urinary Cd is small compared to tobacco consumption [ 13 ]. Our small sample size may have reduced the power to detect an association between SHS exposure and Cd in most groups of our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Placental cadmium levels were higher in women who smoked compared to those who did not smoke [ 83 ] and blood cadmium levels were 3–4 times higher in smokers than non-smokers. Matt et al examined the composition of settled house dust and found that the cadmium and lead components of THS persisted long after smoking ended [ 84 ]. Cadmium in cigarette smoke is known to be a possible cause of lung cancer in smokers, and exposure to lead and cadmium in THS may lead to cardiovascular disease, kidney disease, and osteoporosis [ 85 ].…”
Section: Health Effects Of Thsmentioning
confidence: 99%